Strategi Kepemimpinan Pada Organisasi Mahasiswa Sebagai Upaya Mewujudkan Ketercapaian Program Kerja : (Studi Kasus Organisasi Mahasiswa Fakultas Ekonomi Universitas Tidar) (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
Student organizations play a role in the development of students' managerial and leadership abilities. Human resources in student organizations include leaders and members of the organization. Every student organization certainly has a work program (proker) where this work program is a guide for every step of the organization and also becomes a direction for leaders and members to run the organization's wheels. To carry out this work program, a leadership strategy is needed because this strategy will later provide direction on how the organization can achieve the work program it has set. This study aims to determine how leadership strategies are applied to organizations in order to realize work programs in student organizations. This research uses descriptive qualitative research methods and data processing techniques using SWOT analysis techniques. The population in this study were 15 students who joined the organization at the Faculty of Economics, Tidar University. Based on the results of the study, it was stated that the leadership strategy applied by organizational leaders in directing their members to realize work programs, among others, by providing opportunities for members to participate in decision making, motivating members, directing members to work, and coordinating However, in reality, this strategy still poses obstacles for the organization in the form of delays in carrying out work programs due to lack of discipline among members of the organization.